On the taxonomy of the genus Miltochrista Hübner with descriptions of six new species from the Oriental Realm (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V.; Singh, Santosh; Černý, Karel; Kirti, Jagbir Singh; Datta, Harvinder Singh; Singh, Navneet (Zootaxa, 2025)
The present paper is devoted to the taxonomy of the genus Miltochrista Hübner, [1819] with a special emphasis to the Indian fauna. Six new species of the genus are described: M. gopaldhara Volynkin, Černý, N. Singh, Kirti, Datta & S. Singh, sp. nov. (Northeast India), M. mawphlang N. Singh, Kirti, Datta, S. Singh, Volynkin & Černý, sp. nov. (Northeast India), M. carcharias Volynkin, Černý, N. Singh, Kirti, Datta & S. Singh, sp. nov. (Northeast and South India), M. ephimeces Volynkin, Černý, N. Singh, Kirti, Datta & S. Singh, sp. nov. (Northeast India and northern Myanmar), M. jatinga N. Singh, Volynkin, Černý, Kirti, Datta & S. Singh, sp. nov. (Northeast India, northern Myanmar and Northern Thailand), and M. nuranang N. Singh, Volynkin, Černý, Kirti, Datta & S. Singh, sp. nov. (Northeast India and Nepal). One taxon is reassessed to species level: Miltochrista butleri Leech, [1889], stat. rev. Two new synonyms are introduced: M. neoseriata N. Singh & Kirti, 2016 = M. pseudoseriata N. Singh & Kirti, 2016, syn. nov., and M. floccosa (Walker, [1865]) = Asura violacea Reich, 1936, syn. nov. One synonym is revised: M. floccosa (Walker, [1865]) = Nudaria subcervina Walker, [1865], syn. rev. A neotype is designated for Nudaria subcervina Walker, [1865]. Lectotypes are designated for Asura lacteoflava lacteoflava Rothschild, 1913, Asura lacteoflava aureata Rothschild, 1913, Setina dharma Moore, 1879, Miltochrista butleri Leech, [1889], Lyclene discistriga Moore, 1878, and Sesapa andamana Moore, 1877. The male genitalia of M. paraseriata N. Singh & Kirti, 2016 are correctly illustrated and diagnosed for the first time. Polymorphism of M. dharma is illustrated and discussed. Six species are reported for the first time from the following countries: M. dharma (Moore, 1879) and M. floccosa (Walker, [1865]) from Pakistan and Nepal; M. terminata (Moore, 1878) from Myanmar and Thailand; M. vidlickai Bucsek, 2020 from Vietnam and Thailand; M. quadrata (Holloway, 2001) from Indonesia (Sumatra), Thailand and India (Assam); and M. producta (Černý, 2009) from Nepal and Vietnam. Adults as well as male and female genitalia are illustrated.